KAJIAN PENGARUH PENGGUNAAN NAUNGAN UNTUK TANAMAN SELADA (Lactuca sativa L.) MENGGUNAKAN SISTEM HIDROPONIK NFT (Nutrient Film Technique) - Zaipah Zainal Tuo; Wahida Wahida; Yosefina Mangera (Faculty of Agriculture, Musamus University, 2021)
Lettuce (Lactuca sativa L.) is a high-value horticultural commodity with promising commercial prospects. Farmers in Merauke district have not been able to cultivate lettuce crops evenly due to a variety of factors, including unsuitable climatic conditions, resulting in very limited supply of this crop commodity. The purpose of this study is to examine the effect of using some shade on the growth and yield of lettuce (Lactuca sativa L.) plants grown in a hydroponic NFT (Nutrient Film Technique) system. The research was conducted from July to September 2020 in Samkai village, Merauke, Papua. A Randomized Block Design (RBD) was used in this study. Shade variation in used as the primary tile factor, with four treatments included: without shade. Transparent roof shade, UV plastic shade, and 75% paranet shade. Blocks or repetitions as a factor of 3 subplots. The result indicated that 75% paranet shade provided the optimal plant height and root length value. UV plastic shading could increase the number of leaves and the highest safe weight of 51.13 grams. Meanwhile, transparent roof shading and without shading showed non-optimal result both in growth parameters and lettuce production.